Blocking Kv1.3 potassium channels prevents postoperative neuroinflammation and cognitive decline without impairing wound healing in mice. (September 2020) - Lai, Ieng K.; Valdearcos, Martin; Morioka, Kazuhito; Saxena, Sarah; Feng, Xiaomei; Li, Rong; Uchida, Yosuke; Lijun, An; Li, Wei; Pan, Jonathan; Koliwad, Suneil; Marcucio, Ralph; et al.
Abstract: Background: Postoperative cognitive decline (PCD) requires microglial activation. Voltage-gated Kv1.3 potassium channels are involved in microglial activation. We determined the role of Kv1.3 in PCD and the efficacy and safety of inhibiting Kv1.3 with phenoxyalkoxypsoralen-1 (PAP-1) in preventing PCD in a mouse model. Methods: After institutional approval, we assessed whether Kv1.3-deficient mice ( Kv1.3 –/– ) exhibited PCD, evidenced by tibial-fracture surgery-induced decline in aversive freezing behaviour, and whether PAP-1 could prevent PCD and postoperative neuroinflammation in PCD-vulnerable diet-induced obese (DIO) mice. We also evaluated whether PAP-1 altered either postoperative peripheral inflammation or tibial-fracture healing. Results: Freezing behaviour was unaltered in postoperative Kv1.3 –/– mice. In DIO mice, PAP-1 prevented postoperative (i) attenuation of freezing behaviour (54 [17.3]% vs 33.4 [12.7]%; P =0.03), (ii) hippocampal microglial activation by size (130 [31] pixels vs 249 [49]; P <0.001) and fluorescence intensity (12 000 [2260] vs 20 800 [5080] absorbance units; P <0.001), and (iii) hippocampal upregulation of interleukin-6 (IL-6) (14.9 [5.7] vs 25.6 [10.4] pg mg −1 ; P =0.011). Phenoxyalkoxypsoralen-1 neither affected surgery-induced upregulation of plasma IL-6 nor cartilage and bone components of the surgical fracture callus. Conclusions: Microglial-mediated PCD requires Kv1.3 activity, determined by genetic and pharmacological targeting approaches. Phenoxyalkoxypsoralen-1 blockade of Kv1.3 prevented surgery-induced hippocampal microglial activation and neuroinflammation in mice known to be vulnerable to PCD. Regarding perioperative safety, these beneficial effects of PAP-1 treatment occurred without impacting fracture healing. Kv1.3 blockers, currently undergoing clinical trials for other conditions, may represent an effective and safe intervention to prevent PCD.